1997
DOI: 10.3109/00365549709019029
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis A Outbreak Amongst Intravenous Amphetamine Abusers in Finland

Abstract: This article describes a widespread outbreak of hepatitis A virus (HAV) infection amongst drug abusers in Finland. Although attempts to demonstrate the virus in amphetamines failed, the infection was assumed to be linked to intravenous use of the drug. The unusual mode of transmission prompted us to analyse possible atypical clinical features as well as the spread of the virus to the general population, nowadays practically without protective immunity. Serologically verified cases that occurred in Helsinki wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
2
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 16 publications
2
54
2
2
Order By: Relevance
“…Outbreaks of HAV infection among injection drug users (IDUs) have been reported in North America and Scandinavia (97,101,143). Several routes of transmission are likely to occur, and these include a combination of personto-person and percutaneous spread.…”
Section: Modes Of Transmission and Sources Of Hav Infectionmentioning
confidence: 99%
“…Outbreaks of HAV infection among injection drug users (IDUs) have been reported in North America and Scandinavia (97,101,143). Several routes of transmission are likely to occur, and these include a combination of personto-person and percutaneous spread.…”
Section: Modes Of Transmission and Sources Of Hav Infectionmentioning
confidence: 99%
“…This high rate of infection is rarely seen in North America except in highly endemic regions such as some Alaskan Native and American Indian communities. 2 Although some patients with HCV, predominantly intravenous drug abusers, may be at an increased risk of acquiring HAV compared with the general population, [8][9][10]13,27 this high rate of infection has not been duplicated in studies of North American patients with HCV. 28 The impact of the epidemiology of HAV infection on this decision model is further highlighted in Fig.…”
Section: Figmentioning
confidence: 99%
“…In this study, 41% of those acquiring HAV developed acute liver failure and 86% of these individuals died, a case fatality rate of 35%. 7 Leino et al, 13 on the other hand, reported no deaths among 75 HCV-infected intravenous drug abusers during an outbreak of HAV in Finland.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…HAV occurs worldwide, and humans are thought to be its natural host. The virus is transmitted via person-to-person contact, through the fecal-oral route, and by the ingestion of contaminated food and water (18,26,30,31). The virion is a naked, spherical particle with a diameter of 27 to 32 nm.…”
mentioning
confidence: 99%